Leveraging and exercising caution with ChatGPT and other generative artificial intelligence tools in environmental psychology research - Yuan, Shuai; Li, Fu; Browning, Matthew H. E. M.; Bardhan, Mondira; Zhang, Kuiran; McAnirlin, Olivia; Patwary, Muhammad Mainuddin; Reuben, Aaron (Frontiers in Psychology, 2024)
Generative Artificial Intelligence (GAI) is an emerging and disruptive technology that has attracted considerable interest from researchers and educators across various disciplines. We discuss the relevance and concerns of ChatGPT and other GAI tools in environmental psychology research. We propose three use categories for GAI tools: integrated and contextualized understanding, practical and flexible implementation, and two-way external communication. These categories are exemplified by topics such as the health benefits of green space, theory building, visual simulation, and identifying practical relevance. However, we also highlight the balance of productivity with ethical issues, as well as the need for ethical guidelines, professional training, and changes in the academic performance evaluation systems. We hope this perspective can foster constructive dialogue and responsible practice of GAI tools.